Water pollution - Gay, Kathlyn (New York : F. Watts, 1990)
Discuss the problem of our contaminated rivers, lakes, and oceans and proposes ways to purify them.
Includes bibliographical references (p. 138-140) and index.
Booklist.
School Library Journal.
Wilson's Senior High School.
7.1
7-12.
Keywords: Water quality management -- United States -- Juvenile literature; Water -- Pollution -- United States -- Juvenile literature; Water quality management; Water -- Pollution; Water pollution; Water purification